Social impact of land reclamation at Seri Tanjung Pinang, Pulau Pinang, Malaysia / Nur Syaza Nadhirah Musa and Syed Ahmad Qusoiri Syed Abdul Karim - Musa, Nur Syaza Nadhirah; Syed Abdul Karim, Syed Ahmad Qusoiri (2018)
Reclaiming land is one of the easiest solution to solve the problem of lack of land to be developed.Changes of coastline will give impact on socio-economic development of local communities such as people's income sources.Resident's quality of life reside near the reclaimed area will also decline.Land reclamation activity has contributed to the decrease of fish's catch thus reducing fisherman's income resulting to low quality of life of people.Therefore in this paper the aim is on analyzing the perspective of residents towards land reclamation.The objectives are to determine the factors affecting land reclamation activities towards the residents, to signify the effects of land reclamation towards the residents of Seri Tanjung Pinang, Pulau Pinang and to identify the solutions towards the residents to improve their quality of life.In order to achieve the objectives stated, the methodology being used for this study is through semi-structured interview.Data received will be analyzed using Atlas.ti8 software to get the results.First of all, the researcher carried out a thorough literature review using past published books, magazines, journals and internet.Then interviews were carried out and 12 respondents were being interviewed to collect the required data. It is recommended that the coastal reclamation process on the approval part should consider any temporary and permanent negative impact to the local community.